The correlation between vitamin D deficiency and the severity of painful diabetic neuropathy in patients with type 2 diabetes mellitus (T2DM) - Rizaldy Taslim Pinzon; Putu Clara Shinta Gelgel (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2020)
Background: Diabetes and its complications are the major burden health problem worldwide, and diabetic neuropathy is one of the major complications. Vitamin D levels found to be significantly lower in people with painful diabetic peripheral neuropathy compared with healthy people. The data about the vitamin D levels and severity of the neuropathy in Indonesia are very limited.Objective: This study aims to investigate the possible relationship between vitamin D levels and the severity of diabetic peripheral neuropathy.Methods: A cross-sectional study was carried out during the period from October 2019 to December 2019 on 53 subjects with diabetic peripheral neuropathy. The patient’s clinical profile including age, gender, and duration of diabetes, HbA1c, and associated microvascular complications was documented. The treatment history was recorded from electronic prescribing data. The severity of neuropathy was measured with the Toronto Clinical Neuropathy Scoring System. Serum 25-OH vitamin D levels were measured by enzyme immunoassays for the quantitative measurement of total serum 25-OH Vitamin D level in ng/mL.Results: Vitamin D levels based on the severity of neuropathy are divided into mild, moderate, and severe. At mild neuropathy severity, the average patient's vitamin D level was 19±8.85ng/mL, at moderate severity the patient's vitamin D level was 16.25±6.08 ng/mL, and for severe neuropathy, the average vitamin D level was 13.35±6.20 ng/mL. Spearman correlation test obtained r value= -0.439 and p value=0.001.Conclusions: There is a moderate, significant, and negative patterned correlation between vitamin D level and diabetic peripheral neuropathy severity